Inclusive and Efficient Finance as Catalysts for Foreign Investment in Sub-Saharan Africa - Qamruzzaman, Md; Monika, Monika; Kler, Rajnish (International Journal of Economics and Financial Issues, 2025)
Despite extensive research on external capital flows, limited attention has been given to the joint determinants of remittances and foreign direct investment (FDI) within an integrated financial–institutional–infrastructural framework. Existing studies often assess these flows separately, overlooking the dynamic interdependence between financial inclusion, efficiency, institutional quality, and infrastructural access. This study addresses this gap by examining how these factors simultaneously shape remittance and FDI inflows using a comprehensive panel dataset. Employing advanced econometric approaches—including second-generation panel unit root and cointegration tests, CS-ARDL, AMG, CCEMG estimators, and dynamic System-GMM—the analysis captures long-run equilibrium, short-run dynamics, and addresses endogeneity concerns. The findings reveal that financial inclusion, efficiency, institutional strength, and energy access are significant drivers of both remittances and FDI, though their effects differ in magnitude and persistence across models. By documenting bidirectional causality, particularly between remittances and financial inclusion and between FDI and institutional quality, the study highlights the reinforcing feedback between external flows and domestic systems. These results contribute to the literature by offering an integrated perspective and provide policy insights for strengthening financial deepening, institutional credibility, and infrastructure readiness to mobilize remittances and attract sustainable FDI.